ADAPTATION-ORIENTED APPROACH TO DIAGNOSTICS OF PRENOSOLOGICAL CHANGES IN IN THE STATE OF MENTAL HEALTH OF MODERN PUPILS AND STUDENTS - Serheta , Ihor; Vergeles , Tetiana; Makarova , Olha (Collection of scientific papers «ΛΌГOΣ», 2022)
Prenosological changes in the state of mental health of pupils and students as states that are on the verge of normal and pathological conditions must be considered, analyzed and evaluated based on three fundamental positions: the first position –defines them as a state of health that does not meet the criteria of the average statistical norm and is characterized by the presence of subthreshold mental and behavioral disorders, the second position – as a predisease, the third position – as a violation of the natural course of the processes of mental, psychophysiological and socio-psychological adaptation [2, 3, 6].